Soil Macrofauna: A key Factor for Increasing Soil Fertility and Promoting Sustainable Soil Use in Fruit Orchard Agrosystems - Sofo, Adriano; Mininni, Alba Nicoletta; Ricciuti, Patrizia (Agronomy (Basel), 2020)
Soils and crops in orchard agrosystems are particularly vulnerable to climate change and environmental stresses. In many orchard soils, soil biodiversity and the ecosystem services it provides are under threat from a range of natural and manmade drivers. In this scenario, sustainable soil use aimed at increasing soil organic matter (SOM) and SOM-related benefits, in terms of soil quality and fertility, plays a crucial role. The role of soil macrofaunal organisms as colonizers, comminutors and engineers within soils, together with their interactions with microorganisms, can contribute to the long-term sustainability of orchard soils. Indeed, the continuous physical and chemical action of soil fauna significantly affects SOM levels. This review paper is focused on the most advanced and updated research on this argument. The analysis of the literature highlighted that a significant part of soil quality and fertility in sustainably-managed fruit orchard agrosystems is due to the action of soil macrofauna, together with its interaction with decomposing microorganisms. From the general analysis of the data obtained, it emerged that the role of soil macrofauna in orchards agrosystems should be seriously taken into account in land management strategies, focusing not exclusively on fruit yield and quality, but also on soil fertility restoration.